Recurrent paroxysmal atrial fibrillation induced by marked hypoxia during sleep-disordered breathing - Tobushi, Tomoyuki (J Cardiol Cases, 2016)
Sleep-disordered breathing (SDB) has a big impact on autonomic nervous activity and thus induces or deteriorates various cardiovascular diseases. We here describe a typical but rarely documented case which clearly indicates a strong link between SDB and cardiovascular disease. A 68-year-old woman complaining of frequent palpitations was referred to our institute. An electrocardiogram (ECG) at a previous clinic had shown atrial fibrillation, although it had already returned to sinus rhythm on arrival at our institute. Her body mass index was 32.5 kg/m(2) and she had a history of loud snoring. Simultaneous examinations of Holter ECG monitoring and ambulatory polysomnography (PSG) showed onset of paroxysmal atrial fibrillation following marked oxygen desaturation at midnight. In-hospital PSG revealed severe obstructive sleep apnea. A new device with desaturation triggered ambulatory blood pressure monitoring system performed 1 week later again showed a midnight onset of paroxysmal atrial fibrillation coincided with surge of blood pressure with marked desaturation. Her recurrence of palpitations had obviously decreased by continuous positive airway pressure therapy thereafter. <Learning objective: A clinician should suspect sleep-disordered breathing (SDB) behind cardiac arrhythmia, especially if it is nocturnal. Nocturnal hypertension especially in obese patients may indicate SDB. Successful therapy for SDB by such as continuous positive airway pressure therapy attenuates sympatho-excitation and would improve the result of treatment of the arrhythmia.>